Increase in proline by the application of the biostimuant CBX-103 improves the growth of Arabidopsis thaliana Col 0 under salt stress conditions (Agroindustrial Science, 2024)
Agriculture faces new, increasingly complicated challenges in the face of a constantly changing environment that causes different types of stress in crops, one of them being salinity. Numerous investigations have been carried out to understand the effect of salt stress on the physiology of plants, as well as different ways of dealing with it and creating tolerance and/or resistance so that the productivity of crops is not affected. Among these alternatives we find biostimulants. The biostimulant CBX-103 is composed of carboxylic acids, succinic acids, oligogalacturonides, among others, which are obtained through a controlled enzymatic fermentation of the plant extract of Saccharum officinarum L. In the present study it is demonstrated that foliar applications of the biostimulant CBX- 103 in Arabidopsis thaliana Col 0 plants grown under salt stress increase leaf proline content, significantly reducing the harmful effects of stress, which is demonstrated at a biometric level and regulating growth states. A pathway in the energy regulation of plants is proposed as a mode of action due to the increase in the accumulation of proline obtained and the effect of its components.
Keywords: Arabidopsis thaliana Col 0; bioestimulant CBX-103; carboxylic acids; proline; salt stress